Information Integration of Environmental Preservation Messages to the Students as Young Generations in Gorontalo City - Sri Meylan Mantali; Gita Juniarti; Noval Sufriyanto Talani; Yowan Tamu (MUKADIMAH: Jurnal Pendidikan, Sejarah, dan Ilmu-ilmu Sosial, 2023)
This study analyzes three problems, knowledge, behavior, and media habits, to collect information about environmental preservation. The purpose is to form a strategy for a safe environment based on the data obtained and described. The theory used in this research is integration information theory. The research population is young generations in UNG, and the sample is active students from the Department of Communication at UNG. This study uses a combination of closed and open questionnaires. The results of the research show that the level of knowledge is sufficient. Regarding behavior, students still disagree on several things, such as bringing tumblers to campus. On the other hand, students are supportive if campuses hold open green spaces, create learning curricula about environmental communication, and make policies related to green campuses. Media habits show that students consume more information from social media and entertainment, so environmental preservation information must be included. Therefore, advice was given to the government in Gorontalo to involve young people in preservation programs; mass media, which is more neutral in reporting about the environment; and universities that are starting to improve regarding environmental preservation.